CCR5/CXCR3 antagonist TAK-779 prevents diffuse alveolar damage of the lung in the murine model of the acute respiratory distress syndrome - Chernov, Aleksandr S.; Rodionov, Maksim V.; Kazakov, Vitaly A.; Ivanova, Karina A.; Meshcheryakov, Fedor A.; Kudriaeva, Anna A.; Gabibov, Alexander G.; Telegin, Georgii B.; Belogurov, Alexey A. (Frontiers in Pharmacology, 2024)
Introduction: The acute respiratory distress syndrome (ARDS), secondary to viral pneumonitis, is one of the main causes of high mortality in patients with COVID-19 (novel coronavirus disease 2019)—ongoing SARS-CoV-2 infection— reached more than 0.7 billion registered cases. Methods: Recently, we elaborated a non-surgical and reproducible method of the unilateral total diffuse alveolar damage (DAD) of the left lung in ICR mice–a publicly available imitation of the ARDS caused by SARS-CoV-2. Our data read that two C–C chemokine receptor 5 (CCR5) ligands, macrophage inflammatory proteins (MIPs) MIP-1α/CCL3 and MIP-1β/CCL4, are upregulated in this DAD model up to three orders of magnitude compared to the background level. Results: Here, we showed that a nonpeptide compound TAK-779, an antagonist of CCR5/CXCR3, readily prevents DAD in the lung with a single injection of 2.5 mg/kg. Histological analysis revealed reduced peribronchial and perivascular mononuclear infiltration in the lung and mononuclear infiltration of the wall and lumen of the alveoli in the TAK-779-treated animals. Administration of TAK-779 decreased the 3–5-fold level of serum cytokines and chemokines in animals with DAD, including CCR5 ligands MIP-1α/β, MCP-1, and CCL5. Computed tomography revealed rapid recovery of the density and volume of the affected lung in TAK-779-treated animals. Discussion: Our pre-clinical data suggest that TAK-779 is more effective than the administration of dexamethasone or the anti-IL6R therapeutic antibody tocilizumab, which brings novel therapeutic modality to TAK-779 and other CCR5 inhibitors for the treatment of virus-induced hyperinflammation syndromes, including COVID-19.